由幼稚園教師應具備的資訊素養看大學師培機構資訊科技相關課程之妥適性 Information Technology Literacy: What Kindergarten Teachers Must Know and What Were Taught in Teacher Education Institutions - 吳育蓓 Wu, Yu-Pei; 邱淑惠 Chiu, Shu-hui (National Changhua University of Education, 2009)
本研究探討幼稚園教師應具備的資訊素養與大學幼教師資培育機構規劃之資訊科技相關課程的內容，以瞭解課程規劃是否符合現場老師之需要。本文以問卷調查台灣地區754 位幼稚園教師，瞭解在幼教現場工作應具備之資訊素養，並以內容分析法針對所有蒐集到的幼教師資培育機構開設的18 門資訊科技相關課程大綱進行分類統計。研究結果發現：幼稚園教師認為較應具備的資訊素養為：能使用Word、數位相機、電腦相關儲存設備、流暢的輸入文字，以及能使用與管理電子郵件等基本操作能力，但師資培育機構開設的資訊科技相關課程內容卻偏重於進階多媒體之動畫與網頁製作，兩者呈現不一致的現象。 In this study we surveyed 754 kindergarten teachers to uncover what are the technology skills teachers valued in the field. We also examined the content of technology-related courses through analyzing curriculum syllabus to understand what were taught in teacher education institutions located in Taiwan's universities and colleges. We found that kindergarten teachers valued most the basic technology skills, such as the abilities to use Word and digital cameras, to backup files and to manage e-mail. However, the technology-related courses emphasized more on advanced skills, such as the making of animation and the design of web pages. There is a significant gap between what kindergarten teachers must know and what were taught in teacher education institutions.